2020
DOI: 10.1259/bjr.20200407
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboembolism in hospitalised COVID-19 patients at moderate to high risk by Wells score: a report from Lombardy, Italy

Abstract: Objectives: To present a single-centre experience on CT pulmonary angiography (CTPA) for the assessment of hospitalised COVID-19 patients with moderate-to-high risk of pulmonary thromboembolism (PTE). Methods: We analysed consecutive COVID-19 patients (RT-PCR confirmed) undergoing CTPA in March 2020 for PTE clinical suspicion. Clinical data were retrieved. Two experienced radiologists reviewed CTPAs to assess pulmonary parenchyma and vascular findings. Results: Among 34 patients who underwent CTPA, 26 had PTE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 15 publications
3
31
0
1
Order By: Relevance
“…Similarly, among 34 COVID-19 patients who underwent CTPA, 26 had PE (76%; 20 males, median age 61 years, 77% with comorbidities). 48 Mortality was at 31% in this group. Importantly, 8 PE patients had been under thromboprophylaxis with low-molecular-weight heparin; 4 PE patients had DVT at ultrasound examination.…”
Section: Pulmonary Angiopathy/computed Tomography Findingsmentioning
confidence: 61%
“…Similarly, among 34 COVID-19 patients who underwent CTPA, 26 had PE (76%; 20 males, median age 61 years, 77% with comorbidities). 48 Mortality was at 31% in this group. Importantly, 8 PE patients had been under thromboprophylaxis with low-molecular-weight heparin; 4 PE patients had DVT at ultrasound examination.…”
Section: Pulmonary Angiopathy/computed Tomography Findingsmentioning
confidence: 61%
“… NR NR Mirsadraee et al [ 68 ] UK March 19–June 23 -72 -Mean 52 years (± 10) -53 males Routine in all patients who are admitted to ICU 12 patients (16.7%) Two consultant cardiothoracic radiologists, with disagreements resolved by consensus. Miró et al [ 67 ] Spain and France March 6–April 15 -320 -NR -NR PE suspected based on patient signs and symptoms NR NR Moll et al [ 69 ] USA March 7–April 13 -25 -NR -NR NR NR NR Monfardini et al [ 70 ] Italy March 1–March 31 -34 -NR -NR Sudden oxygen desaturation coupled with a moderate to high risk of PE according to the Wells score and D-dimer levels 8 patients (23.5%) Two experienced thoracic radiologist with 15 and 20 years of experience Mouhat et al [ 71 ] France March 15–April 16 -162 -Mean 65.57 years (± 13.00) -109 males Oxygen saturation measured by pulse oximetry ≤ 93% in room air, breathing rate of ≥ 30 breaths/minute or rapid clinical worsening 141 patients (87.0%) Two chest radiologists Mueller-Peltzer et al [ 72 ] Germany March 8–April 15 -16 -Mean 62.2 years (range 47–77) -10 males When likelihood of PE was considered high 4 patients (25%) Two radiologists with 6 and 13 years of experience in thoracic radiology O'Shea et al [ 73 ] USA March 17–April 6 -94 -NR -NR NR NR Radiologist with 7 years of experience in cardiovascular imaging Ooi et al [ 74 ] UK March 1–April 30 …”
Section: Resultsmentioning
confidence: 99%
“…Ventura-Díaz et al 20 Espallargas et al 25 Mueller-Peltzer et al 26 Ramadan et al 27 Mouhat et al 30 Alonso-Fernández et al 32 Monfardini et al 39 Freund et al 40 Chen et al 41 Whyte et al 43 Fauvel et al 45 Larsen et al 48 Bavaro et al 51 Mazzaccaro et al 53 Gervaise et al 54 Poyiadji et al 60 Bompard et al 62 BDL Overall (I 2 = 94.8%) patients with severe COVID-19. 68 It has been suggested that SARS-Cov-2 in severe forms of the disease induces an excessive inflammatory state via cytokine storm combined with endothelial injury and pulmonary vascular microthrombosis, which could considerably increase the risk for VTE, mainly PE.…”
Section: Table 1 (Continued)mentioning
confidence: 99%